The Optimality of a Simple Market Mechanism - Mark A. Satterthwaite; Steven R. Williams (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1999)
Strategic behavior in a finite market can cause inefficiency in the allocation, and market mechanisms differ in how successfully they limit this inefficiency. A method for ranking algorithms in computer science is adapted here to rank market mechanisms according to how quickly inefficiency diminishes as the size of the market increases. It is shown that trade at a single market-clearing price in the k-double auction is worst-case asymptotic optimal among all plausible mechanisms: evaluating mechanisms in their least favorable trading environments for each possible size of the market, the k-double auction is shown to force the worst-case inefficiency to zero at the fastest possible rate.
Keywords: 330